PENINGKATAN PRESTASI BELAJAR IPA SISWA KELAS VI MELALUI IMPLEMENTASI METODE DISCOVERY DI SDN 1 WATES KEC. SLAHUNG KAB. PONOROGO TAHUN PELAJARAN 2014/2015 - Daris, Daris; Sunardi, Sunardi; Hariyadi, Nugraha (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2023)
The purpose of this research is to increase the science learning achievement of class VI students through the implementation of the discovery method at SDN 1 Wates Kec. Slahung Kab. Ponorogo 2014/2015 Academic Year. This research is an action research (action research), because the research was conducted to solve learning problems in the classroom. This research refers to continuous improvement of learning. This research uses the action research model from Kemmis and Taggart (1988), which is in the form of a spiral from one cycle to the next. Each cycle includes planning (plan), action (action), observation (observation), and reflection (reflection). This research was conducted for three cycles/rounds. The observation was divided into three rounds, namely rounds 1, 2 and 3, where each round was subjected to the same treatment (same activity flow) and discussed one sub-topic which ended with a formative test at the end of each round. This research took place at SDN 1 Wates, Kec. Slahung Ponorogo Regency 2014/2015 academic year. The research subjects were 23 students of class VI at SDN 1 Wates. This research was carried out through 5 stages, namely, (1) planning stage, (2) preparation stage, and (3) implementation stage, (4) data processing stage, and (5) report preparation. The instruments used in this study consisted of: observation sheets of teaching and learning activities, observation sheets of student activities, and formative tests. In this study using descriptive qualitative analysis techniques. The results showed: (1) learning by discovery had a positive impact on improving student achievement which was marked by an increase in student mastery in each cycle, namely cycle I (56%), cycle II (73%), cycle III ( 91%); and (2) the application of the discovery learning method has a positive influence, which can increase student motivation and achievement.